Limited Face-to-face Lectures at a State University During the Pandemic - Virgiawan Listanto (Universitas Islam Negeri Walisongo, 2022)
The Directorate General of Higher Education, Research and Technology has issued Circular Letter 4 of 2021 concerning implementing Face-to-face Learning for the Academic Year 2021/2022. Universitas Negeri Semarang (UNNES) has responded by giving Circular Letter Number: B/11898/UN37/KM/2021 concerning hybrid Lectures for Odd Semester 2021/2022 in Universitas Negeri Semarang. Limited face-to-face lectures during the Covid-19 pandemic came up with many challenges and required rigorous preparation. It is because UNNES will not take any actions that put both its employees and students at risk. This study uses a qualitative research approach framework that describes a phenomenon and information related to implementing hybrid learning during the pandemic. UNNES has successfully implemented both preparation and implementation stages according to the guideline. No Covid-19 cases have been found caused by performing mixed class. However, there is still a concern about the absence of temporary isolation rooms for academics and students with Covid-19 symptoms/criteria. This part is compulsory based on the circular letter issued by The Directorate General of Higher Education, Research and Technology. It has not been fulfilled yet in almost every department with a hybrid class.